Partial discharge and breakdown strength of cross-linked plyethylene nanocomposits containing plasma-treated silicon dioxide nanoparticles - Mat Saman, Norhafezaidi (2022)
Polymer nanocomposites are promising formulations and an inspiring route for developing innovative polymeric-based insulating materials. However, the agglomeration of nanoparticles within the polymer matrix is the main factor that restricts the enhancement of insulation characteristics because the non-uniform dispersion of nanoparticles consequently reduces the interfacial area and creates weak polymer-nanofiller interfacial bonds. Conventionally, the chemical surface functionalization and calcination techniques have been introduced to modify the surface of nanoparticles in enhancing the compatibility between the nanoparticles and polymer matrix. However, these techniques were unsuitable for implementation because they required complex sequential steps. Thus, this research proposed an alternative technique of nanoparticle surface modification using atmospheric pressure plasma (APP) to improve the surface compatibility of nanoparticles and polymer matrix, consequently leading to the enhancement of dielectric properties such as partial discharge (PD) resistance and alternating current (AC) breakdown strength. This thesis also explores the effect of plasma treatment and its correlation to the aforementioned dielectric properties. In this study, the optimum operating parameters of APP, such as voltage supply, excitation frequency, and working gas flow rate have been characterized to acquire homogeneous and stable plasma discharge, which is then used to treat the surface of silicon dioxide (SiO2) nanoparticles in enhancing its compatibility with cross-linked polyethylene (XLPE) matrices. The weight percentages of untreated and plasma-treated SiO2 nanoparticles dispersed into XLPE were manipulated to 1 wt%, 3 wt%, and 5 wt%, as well as the duration of treatment that manipulated to 1 minute, 3 minutes, and 5 minutes to identify the most effective formulation of XLPE/SiO2 nanocomposites. As aforementioned, the optimum operating parameters for producing homogeneous and stable plasma discharge were 0.5 kV, 20 kHz, and 0.8 L/min, respectively. In comparison with unfilled XLPE, the most effective formulation of XLPE nanocomposites was shown by the sample with 3 wt% of 5-minute plasma-treated SiO2 nanoparticles with the highest PD resistance with the reduction of PD magnitude up to 2000 pC, the reduction of PD number up to 220512, and the reduction of surface roughness due to PD attacked up to 1.04 p,m. Meanwhile, the same formulation of XLPE nanocomposites also indicated the most significant enhancement of AC breakdown strength up to 26.29 kV/mm compared to unfilled XLPE. Plasma has been found to be an alternative technique to improve the PD resistance and AC breakdown strength of XLPE nanocomposites by exciting the formation of the more substantial interfacial regions through the formation of interfacial bonds and the reduction of the size and number of agglomerated clusters. It is inferred that the plasma treatment method is appropriate for producing nanocomposites with improved surface compatibility and enhancing polymer nanocomposites' dielectric properties for high voltage insulation material applications.